PENGARUH DISIPLIN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT BIRU LAKSANA UTAMA JAKARTA SELATAN - Pramudito, Bayu; Januar Rukmana, Indra (Journal of Research and Publication Innovation, 2024)
The purpose of this research is to determine the influence of work discipline and work motivation on employee performance at PT Biru Laksana Utama. The method used is quantitative. The sampling technique used a saturation formula and a sample of 60 respondents was obtained. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficients, coefficients of determination and hypothesis testing. The results of this research are that work discipline has a significant effect on employee performance with a coefficient of determination value of 59.1% and the hypothesis test obtained t count > t table or (9.158 > 2.002). Work motivation has a significant effect on employee performance with a coefficient of determination value of 67.1% and hypothesis testing obtained t count > t table or (10.882 > 2.002). Work discipline and work motivation simultaneously have a significant effect on employee performance with the regression equation Y = 2.706 + 0.377 X1 + 0.589 X2. The coefficient of determination value is 86.5% while the remaining 13.5% is influenced by other factors. Hypothesis testing obtained a calculated F value > F table or (84.393 > 3.15).